Afamin: an early predictor of preeclampsia - Köninger, Angela (Arch Gynecol Obstet, 2018)
PURPOSE: Oxidative stress is involved in the pathogenesis of hypertensive disorders such as preeclampsia (PE) and associated with the human vitamin E-binding protein afamin. The aim of this study was, therefore, to analyse afamin in the first trimester of patients developing PE later in pregnancy and in control subjects without pregnancy complications. METHODS: In this retrospective study, 137 serum samples from the first trimester of pregnancy were analysed in a case–control study design. 39 patients developed PE (10 patients with early-onset and 29 patients with late onset disease) and 98 women had an uncomplicated pregnancy. Mann–Whitney U test, t test, logistic regression and ROC analyses were performed for statistical evaluation. RESULTS: Pregnant women developing PE presented with higher afamin concentrations in the first trimester [median 101.81 mg/L; interquartile range (IQR) 88.94–113.26] compared to subjects with uncomplicated pregnancy (median 86.40; IQR 75.26–96.92; p < 0.001). After adjusting for confounders, the odds ratio per afamin standard deviation was 1.60 (95% CI: 1.04–2.58; p = 0.04). An afamin threshold concentration of 87.8 mg/L exhibited the best sensitivity (79.5%) and specificity (57.1%) in predicting PE. Subgroup analysis of early- and late-onset disease resulted in substantially higher afamin concentrations in women with developing late-onset PE compared to controls (p < 0.001) with an odds ratio per afamin standard deviation of 1.62 (95% CI: 0.98–2.70; p = 0.06). CONCLUSIONS: Serum afamin concentrations are elevated in the first trimester among patients developing PE compared to controls. Substantial differences were observed mainly among patients with late-onset PE.